A Profit Optimization Using Linear Programming Method on XYZ Convection - Nabila, Putri Isma; Tahyudin, Imam; Munandar, Aris; Ananda, Fahesta (Internet of Things and Artificial Intelligence Journal, 2022)
Optimal production planning is one of the essential aspects of achieving company targets. Errors in planning production result in non-maximum profit gains. Furthermore, there needs to be a method to avoid mistakes in production planning, and it is necessary to use the proper technique. Xyz Convection is one of the businesses producing unique clothing for pants. This study aims to determine the optimization of XYZ convection production in maximizing profits using linear programming. Surveys and interviews with business owners of Xyz Convection carried out data collection. The data obtained are in the form of data on the use of raw materials, operating costs, margins, and selling prices. The amount of raw material inventory of jeans fabric in the 1st week is 550, in the 2nd week is 775, in the 3rd week is 550, and in the 4th week is 650. The method used in this study is linear programming, using the simplex method. The optimal solution is to obtain maximum profit from the production of convection pants every week with a fund of 21,000,000 IDR to produce 1.167 pcs of cotton shorts, where the company will earn a profit of 35,010,000 IDR with expenses less than the existing funds, which is 20,982,147 IDR.